Respuesta :
to find the inverse of f(x),,
replace f(x) with y
switch x and y
solve for y
replae y with f infverse or f^-1(x)
h(x)=6x+1
replace
y=6x+1
switch
x=6y+1
solve
x-1=6y
(x-1)/6=y
replace
h^-1(x)=(x-1)/6
D is answer
replace f(x) with y
switch x and y
solve for y
replae y with f infverse or f^-1(x)
h(x)=6x+1
replace
y=6x+1
switch
x=6y+1
solve
x-1=6y
(x-1)/6=y
replace
h^-1(x)=(x-1)/6
D is answer
Answer: Option 'D' is correct.
Step-by-step explanation:
Since we have given that
[tex]h(x)=6x+1\\[/tex]
We need to find the inverse of h .
Let,
[tex]h(x)=y[/tex]
the our equation becomes,
[tex]y=6x+1\\\\y-1=6x\\\\\frac{y-1}{6}=x[/tex]
Now, interchange x with y :
[tex]\frac{x-1}{6}=y[/tex]
so, our inverse of h will be
[tex]h^{-1}(x)=\frac{x-1}{6}[/tex]
Hence, Option 'D' is correct.